Development of Learning Interactive Media Assisted by Google Sites in the Subject of Light Wave for Increased Learning Outcome and Learning Motivation - Halwiah; Subaer; Khaeruddin (PT FORMOSA CENDEKIA GLOBAL, 2026)
The integration of interactive digital media in physics learning is essential to address students’ difficulties in understanding abstract concepts such as light waves. This study aims to develop and evaluate interactive learning media assisted by Google Sites for light wave material. The research employed a Research and Development approach using the ADDIE model. The participants were 31 twelfth-grade students and one physics teacher. Data were collected using validation sheets, learning outcomes tests, motivation questionnaires, and response questionnaires. The results indicated that the developed media met the criteria of validity, effectiveness, and practicality. The average validity score reached 97.31%, while the classical completeness of learning outcomes was 96.77% with a mean score of 85.87. Students’ learning motivation increased by 18.72%, supported by the Wilcoxon test showing that all students experienced improvement. The practicality was reflected in positive responses from students (83.14%) and teachers (100%). These findings demonstrate that Google Sites-assisted interactive media effectively enhances students’ conceptual understanding and learning motivation, particularly in learning abstract physics concepts, and supports the implementation of student-centered learning in the digital era.